Gaya Kepimpinan Transformasi Islam Berdasarkan Perbezaan Kumpulan Jawatan : Islamic Transformation Leadership Style Based on Differences In Job Groups - Nurshahira Ibrahim,; Rasyad Afif Ibrahim ,; Sakinatul Raadiyah Abdullah ,; Ramlan Mustapha ,; Lokman Abdul Rasol , (Online Journal of Research in Islamic Studies, 2021)
Transformation is a process of change that needs to be implemented by a leader in emphasizing the Islamic aspect in his leadership so that each of his followers is aware of the responsibilities and beliefs that are borne in performing the task. This study aims to measure the relationship between transformational leadership style, psychological empowerment, and employee creativity by applying the Islamic approach to managing organizations based on two position groups: professional management and implementing groups. This study uses 292 questionnaires obtained from employees working in Islamic financial institutions, Malaysia. Smart Partial Least Squares (SmartPLS) path model analysis was used to perform hypothesis testing and PLS-MGA. This study shows that transformational leadership has a positive and significant relationship to employees' psychological empowerment and creativity based on two different groups, namely the professional management group and the implementing group. Overall, this study confirms that transformational leadership is one of the important determinants of employee psychological empowerment and creativity. Further, discussions, implications, and conclusions are elaborated in this study.